2020
DOI: 10.1186/s12944-020-01391-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of leptin in selected skin diseases

Abstract: Leptin is an adipokine, adipocyte-derived compound, which acts both as a hormone and cytokine. It is mainly synthesized by adipocytes of white adipose tissue. Leptin possesses pleiotropic functions including, among others, stimulation of angiogenesis and production of proinflammatory cytokines. The various types of leptin activity are related to the wide distribution of leptin receptors. This adipokine acts by activating intracellular signaling cascades such as JAKs (Janus kinases), STATs (signal transducers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 114 publications
(230 reference statements)
0
30
0
Order By: Relevance
“…In adaptive immunity, leptin polarizes T cells towards a Th1 response via stimulating the production of IL2, IL12 and IFN γ and inhibiting IL10 and IL4, and leptin signaling positively regulates Th17 differentiation and negatively regulates the regulatory T cell (Treg) function via the mTOR pathway (Dopytalska et al, 2020, Perez-Perez et al, 2020. Further, leptin can stimulate the proliferation of keratinocytes, fibroblasts and endothelial cells, promoting epidermal/dermal hyperplasia and angiogenesis (Dopytalska et al, 2020). Together, J o u r n a l P r e -p r o o f elevated serum leptin levels in obesity may contribute to the low-grade inflammatory state which make obese individual more susceptible to the development of autoimmune diseases.…”
Section: 2psoriasis and Adipokines: Leptin And Adiponectinmentioning
confidence: 99%
“…In adaptive immunity, leptin polarizes T cells towards a Th1 response via stimulating the production of IL2, IL12 and IFN γ and inhibiting IL10 and IL4, and leptin signaling positively regulates Th17 differentiation and negatively regulates the regulatory T cell (Treg) function via the mTOR pathway (Dopytalska et al, 2020, Perez-Perez et al, 2020. Further, leptin can stimulate the proliferation of keratinocytes, fibroblasts and endothelial cells, promoting epidermal/dermal hyperplasia and angiogenesis (Dopytalska et al, 2020). Together, J o u r n a l P r e -p r o o f elevated serum leptin levels in obesity may contribute to the low-grade inflammatory state which make obese individual more susceptible to the development of autoimmune diseases.…”
Section: 2psoriasis and Adipokines: Leptin And Adiponectinmentioning
confidence: 99%
“…It can be supposed that the LEP receptor changes its expression following the stimulation of the increased plasma LEP since hormone local production was not changed. The increased LEPR expression observed in the Obese group suggests that the receptor plays a modulating role in the skin system control and that serum LEP may have a role in the pathogenesis of skin disease associated with obesity [61]. However, Arnold et al [62] have shown that among the different isoforms of LEPR (LEPRa, b, c, d, f: transmembrane), there is also a soluble form of the LEP receptor (LEPRe) capable of modulating the bio-availability and the consequent action of LEP.…”
Section: Discussionmentioning
confidence: 98%
“…This is an interesting issue to be further considered. The presence of a soluble receptor form, which captures the available plasma LEP, could explain the general impaired full functionality of LEP (LEP resistance), as well as, the skin reaction represented by LEPR over-expression, thus testifying to a possible involved cause in the well-documented skin disorders in obese subjects [61].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity promotes a low-grade, chronic inflammation mediated by the secretion of hormones and cytokines, including leptin [ 25 ], which has been demonstrated to stimulate the production of pro-inflammatory cytokines in immune cells [ 26 ] as well as inducing reactive oxygen species [ 27 ]. Leptin is a soluble peptide hormone consisting of 167 amino acids whose existence was predicted for the first time in the 1950s and 1960s on leptin deficient (ob/ob) and leptin receptor deficient (db/db) mice [ 28 , 29 ], although it was finally described in 1994 as the product of the obese (Ob or LEP) gene [ 30 ], with a structure similar to the long-chain helical cytokine family, which includes interleukin (IL) 6, IL-11, IL-12, G-CSF or oncostatin M, among others [ 31 ].…”
Section: Leptin At a Glancementioning
confidence: 99%
“…One of the most important pro-inflammatory obesity-related adipokines is leptin, which has pleiotropic functions [ 24 ]. Moreover, overweight and obesity were associated with an increased risk of this disorder, thus suggesting a relationship between leptin and skin diseases such as atopic dermatitis (AD) [ 25 ]. For this reason, the purpose of this article is to review the available literature related to the possible role of this adipokine in AD, and to take leptin into account as a possible biomarker in the disease.…”
Section: Introductionmentioning
confidence: 99%